Кинетика и механизмы десорбции метана из угля - Алексеев, А.Д.; Васильковский, В.А.; Калугина, Н.А. (Физико-технические проблемы горного производства, 2005)
Теоретично обґрунтовано новий метод аналізу кінетики десорбції метану з кам'яного вугілля. Застосування цього методу щодо трактування результатів експерименту дозволяє з'ясувати механізми виходу газу (дифузія, фільтрація або їх суперпозиція). The new method of the analysis of kinetics of desorption of methane from coal is proved theoretically. Application of this method at treatment of results of experiment allows to find out the mechanism of an output of gas (diffusion, a filtration or their superposition).